1994
DOI: 10.1136/jnnp.57.11.1360
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism after recurrent insulin induced hypoglycaemic episodes: a PET study.

Abstract: Neuropsychological testing was carried out and the rate of oxygen metabolism in the brain was measured by PET in 15 highly selected patients with type 1 diabetes. The aim was to investigate the impact on the brain of hypoglycaemic comas resulting from insulin treatment. No significant difference was found between nine patients with a history of more than 10 hypoglycaemic comas and six others who denied any history of such events. These data suggest that intensified insulin treatment, although increasing the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…We observed that the pattern and severity of cognitive changes in study populations of adult diabetic patients with an average age at diabetes onset Ͻ15 years were comparable to those with an average age at onset above this age. It should be noted, however, that studies that assessed cognition in children with diabetes (which were not included in the present metaanalysis) observed that a very early age at onset (before the age of 5 years) does ap- 29 -31,36,37,39,41), b ϭ (29,30,36,41), c ϭ (4,31,37,39,41), d ϭ (29,36,37,39), e ϭ (29,37,39), f ϭ (30,37,39,41), g ϭ (29,36), h ϭ (4,39,41), i ϭ (29,31,37,39,41), j ϭ (4,29,36,37,39), and k ϭ (29,39) pear to be associated with more severe impairments of cognitive performance (11,46). Our meta-analysis does not support the idea that there are important negative effects from recurrent episodes of severe hypoglycemia on cognitive functioning.…”
Section: Conclusion -mentioning
confidence: 82%
See 1 more Smart Citation
“…We observed that the pattern and severity of cognitive changes in study populations of adult diabetic patients with an average age at diabetes onset Ͻ15 years were comparable to those with an average age at onset above this age. It should be noted, however, that studies that assessed cognition in children with diabetes (which were not included in the present metaanalysis) observed that a very early age at onset (before the age of 5 years) does ap- 29 -31,36,37,39,41), b ϭ (29,30,36,41), c ϭ (4,31,37,39,41), d ϭ (29,36,37,39), e ϭ (29,37,39), f ϭ (30,37,39,41), g ϭ (29,36), h ϭ (4,39,41), i ϭ (29,31,37,39,41), j ϭ (4,29,36,37,39), and k ϭ (29,39) pear to be associated with more severe impairments of cognitive performance (11,46). Our meta-analysis does not support the idea that there are important negative effects from recurrent episodes of severe hypoglycemia on cognitive functioning.…”
Section: Conclusion -mentioning
confidence: 82%
“…Eleven studies addressed the role of metabolic control, defined as a dichotomous variable, on cognition (3,7,21,28,30,(33)(34)(35)37,42,43) (Table 2). A qualitative analysis of the data presented in Table 3 shows no consistent difference between the "well" and "poorly" controlled groups.…”
Section: -Standardized Effect Sizes (Cohen's D) and 95% Cis For The Cmentioning
confidence: 99%
“…If such a biomarker can be developed, future study could focus on identifying interventions that can prevent the appearance or slow the progression of white matter microstructural changes in patients with diabetes. Over the last 10 years, investigators have used a variety of imaging techniques, including MRI, single photon emission computed tomography (30,31), and positron emission tomography (32), to determine whether structural abnormalities could be identified in the brains of patients with (36), and decreased cerebral gray matter density (37,38) in type 1 diabetic subjects. Some of these structural abnormalities have corresponded to age of diabetes onset (35), A1C levels, hypoglycemia (37), and the presence of retinopathy (38).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients who have a history of recurrent, severe hypoglycemia, the regional blood flow changes were observed to be present during normoglycemia and may represent a cerebral adaptation to recurring hypoglycemic insults (39,40). In a study performed by Chabriat et al (41), no differences were found in neuropsychological test performance and rate of oxygen metabolism measured by position emission tomography scanning in patients with a history of Ͼ10 hypoglycemic comas compared with those without a history of comas. Patients with angiopathic complications were excluded.…”
Section: Diabetes Vol 55 February 2006mentioning
confidence: 93%